Kazakhstan in a Context of Growing Competition between the USA and China (International relations and international law Journal, 2023)
The Republic of Kazakhstan is a state that has reached a certain level of regional influence and international recognition. To date, Kazakhstan has managed to build partnerships with all countries of the region, based on the principles of parity of the parties. Using a multi-vector approach in building foreign policy, Kazakhstan considers diplomatic efforts as a means of developing a network of stable relations both with the states of the region and with other actors in world politics. The complex of threats that endanger the security and sovereignty of the country is constantly growing and changing. The aggravated geopolitical situation both on the continent and around the world can lead to the emergence of a regional conflict and escalate existing points of tension. Given its specific geopolitical location, it appears that Kazakhstan needs to be careful in its partnership architecture. This study considers scenarios of confrontation between the United States and China as the two largest economies in the world and ideological antagonists in the context of direct and indirect impact on Kazakhstan, including through the implementation of the strategy of applying "soft power" to the countries of the region.The growing risks of many stress scenarios for the entire world community require a multipolar, balanced policy based on the principles of pragmatism. The importance of conducting an impact assessment is due, among other things, to the fact that Kazakhstan shares a fairly long border with China. Based on the analysis and assessment carried out, it was concluded that it is necessary to adapt the foreign policy of Kazakhstan to the ongoing processes and develop its own, unique development path that meets the interests of the state and ensures its security.Keywords: Kazakhstan, China, USA, Central Asia, multi-vector approach, geopolitics, regional influence, sovereignty, international relations.